Análisis de instalaciones eléctricas en bodegas - Vera Martínez, Rómulo Javier (2011)
This work is to evaluate and implement control measures necessary to avoid the effects of existing risk factors in electrical systems, meeting the Ecuadorian standard as safety and health’s regulation of workers and improved working environment - Decree 2393, ISO 2631 and 5349, the Mexican Standards NOM-001-based 2005 to electrical installations in warehouses, and other standards of interest. All work is done with the help of qualitative and quantitative methods which are preliminary hazard analysis, risk assessment and the checklist, with which examines the electrical risks and associated in electrical installations in a paint and solvent’s warehouse. Electricity’s risk, fire, explosion, poisoning inside the warehouse. Also, some recommendations are given to safe operation of electrical installations, based on the risks that may affect people who are exposed to the hazards of the installation.